2014
DOI: 10.1002/jmri.24823
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of apparent diffusion coefficient associated with pathological grade of lung carcinoma, before therapy

Abstract: ADC measurement of lung cancer was a helpful method to evaluate the pathological grade and tumor cellular density. The quantitative analysis of ADC in conjunction with conventional MR findings could provide more valuable information for the assessment of pulmonary tumor. J

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
(88 reference statements)
2
21
1
Order By: Relevance
“…Low ADC represents restricted diffusion and is found in highly cellular regions such as tumours and normal lymph nodes. Reports correlating ADC with NSCLC pathology specimens have confirmed a decrease in tumour ADC with increasing cellularity (as previously reported for other body parts), and an ADC cut-off can be set such that DW-MRI differentiates grade III cell density from lower grades with a sensitivity of 88.2% and a specificity of 62.5% [59,60].…”
Section: Tumour Microenvironmentmentioning
confidence: 59%
“…Low ADC represents restricted diffusion and is found in highly cellular regions such as tumours and normal lymph nodes. Reports correlating ADC with NSCLC pathology specimens have confirmed a decrease in tumour ADC with increasing cellularity (as previously reported for other body parts), and an ADC cut-off can be set such that DW-MRI differentiates grade III cell density from lower grades with a sensitivity of 88.2% and a specificity of 62.5% [59,60].…”
Section: Tumour Microenvironmentmentioning
confidence: 59%
“…Since radiotherapy is highly capable of reducing proliferation and activating cell death mechanisms such as apoptosis, with subsequent disintegration of membrane structures, ADC and D are both potent candidates for radiotherapy response assessment [2] , [36] . Several studies have shown that ADC is related to both cellular density and tumor aggressiveness [10] , [8] , [37] , [45] , [39] , [40] , [41] , [42] . Rijswijk et al [43] compared diffusion estimated by D with ADC in soft tissue tumors in patients with tumors of different type and location.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging-histopathological comparison study is helpful to identify the cause of overlapping ADC values between malignant and benign SPLs. Several histopathological parameters, such as cell density, nuclear-to-cytoplasm ratio (NCR), necrotic fraction and grade of differentiation, have been previously quantified and some were shown to be significantly correlated with ADC value in malignant SPLs 18 22 . However, to the best of our knowledge, the overall effects of these histopathological parameters on ADC value have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%